Social Attitudes formation through character and Islamic Education Learning in Class IV Elementary School Students in West Jakarta - Mawardi, Mawardi; MS, Zulela; Sumantri, Mohamad Syarif (International Journal for Educational and Vocational Studies, 2020)
The purpose of this study was to determine the formation of social attitudes through character and Islamic Education learning in class IV students of West Jakarta Elementary Schools. This study uses qualitative methods with data collection techniques such as observation, interviews, questionnaires and documentation. Data sources involve teachers and students. Data analysis techniques used the Mliles and Huberman models through the stages of reduction, display, and data verification. The results showed that learning related to the development of social attitudes was not running optimally, due to: 1) the role of teachers who did not comprehensively understand the 2013 curriculum, the teacher did not design learning strategies that focused on increasing the social attitude competencies that existed in core competencies (KI -2) both the media up to the evaluation that measures the development of students' social attitudes, 2) there are still obstacles such as uneven facilities, lack of socialization, teachers and students do not understand the contents of the curriculum as a whole. Meanwhile, the solution in dealing with the problem of implementing the 2013 curriculum in the subjects of character and Islamic Education learning  is: an increase in teacher competency in designing, and developing Learning models that meet the needs of teachers and students, especially those related to social attitude competencies.